Standards for nursing education in the Commonwealth Caribbean : accountability (PAHO/WHO Washington, DCUS, 1999)
Presents a revised set of standards to be used for the internal and external evaluation of the performance of nursing schools in the Commonwealth Caribbean.
Includes Guidelines for scoring standards of nursing education in the Commonwealth Caribbean. 1998. 33 p.